The Role of Motivation, Learning Discipline and Competence in Improving Learning Achievement - Siska Aprelyani (Siber Nusantara Review, 2024)
The Role of Motivation, Learning Discipline and Competence on Learning Achievement. The aim is to analyze the role of motivation, learning discipline and competence on learning achievement. The method of writing this scientific article is by using the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other online media. The results of this study are: 1) Motivation plays a role in Learning Achievement, 2) Learning Discipline plays a role in Learning Achievement, 3) Competence plays a role in Learning Achievement. Apart from these 2 exogenous variables that affect the endogenous variable of Education Quality, there are still many other factors including the environment, organizational culture, curriculum.